A heterogeneous pore decoration strategy on a hydrophobic microporous polymer for high-coverage capture of metabolites. Issue 52 (28th May 2020) - Liu, Shuqin; Fang, Shuting; Huang, Yiquan; Xiang, Zhangmin; Ouyang, Gangfeng
Abstract : A heterogeneous pore decoration strategy on a hydrophobic microporous polymer resulted in its hydrophobic–hydrophilic hybrid properties and high-coverage capture ability of microbial metabolites. Abstract : Herein, a heterogeneous pore decoration strategy on a hydrophobic microporous polymer is presented. The smaller pores in the material were completely decorated with hydrophilic polydopamine while most of the larger ones survived after modification, leading to its hydrophobic–hydrophilic hybrid properties and high-coverage capture ability of metabolites.